A new record of the giant freshwater prawn, Macrobrachium spinipes (Schenkel, 1902) (Crustacea: Decapoda: Palaemonidae) from Taiwan, with notes on its taxonomy - Shy, Jhy-Yun; Wowor, Daisy; Ng, Peter K. L. (Zootaxa, 2013)
The giant freshwater prawn Macrobrachium spinipes (Schenkel, 1902) is recorded from Taiwan for the first time and extends the distribution of the species to north of the Tropic of Cancer. The Taiwanese specimens differ slightly from material from Indonesian Papua in the density of the spination of the adult second pereipods, the relative length of the ridge of the posterior submedian plate of thoracite sternite 4, and the color of the carapace, abdomen and pleural condyles.